The Significance of Higher Education in Facilitating Labour Market and Student Migration in Fiji - Gosai, Sharnit (Acta Pedagogia Asiana, 2025)
In Fiji, labour shortages have significantly increased over the past decade. As the education system improved, many individuals opted to migrate in search of better educational opportunities and job prospects abroad. The policy brief focuses on the impact of migration on individuals seeking adequate education and training. It is evident that a growing number of people chose to pursue further education by moving abroad. As highlighted in the National Economic Summit, migration abroad for educational, employment, or permanent purposes is a significant factor. This poses a considerable challenge to Fiji's economic progress, as the country faces a shortage of skilled and educated workers to meet the demands of the labour market. As Fiji advances in its development, these shortages could have serious implications for the nation's future. It is crucial for all stakeholders, including policymakers, educators, economists, and other professionals, to play their part in addressing these issues. Without enough skilled and educated workers, Fiji may struggle to maintain its position. Over time, the country may have fewer local individuals contributing innovative and creative ideas, leading to a decline in human capital formation, which could persist as a long-term issue. The present study constitutes an analytical research paper that investigates the effects of student and labour migration on economic development and labour market dynamics. Special attention is given to the role and contributions of higher education in shaping these impacts.